El caserío es la unidad productiva en la articulación organizacional de zonas rurales altoandinas, Callejón de Huaylas, Ancash - Paredes Tarazona, Mildred (2009)
The object is to specify three significant indicators identified for the joint organizational highland rural areas supported by economic psychology, and studies were conducted in the villages Queral, Miramar, Chinchay, the Rural Community Pampacocha Cruz de Mayo, since 2003, population over 16 years, the results indicate that hamlet variable discriminates more effectively between the psychosocial dimensions of their social construction of social organization for organizational representation of the peasant community, likewise, is one that produces synergy by the perception its members to the knowledge of the demand to form economic interdependencies between villages, and discriminates against the perception of working conditions of the competition by providing environmental management to the Community. It has been used perceptions scales valid and reliable for each research and economic actors of each consumer unit were surveyed in Quechua in the area by a designated representative of the Community.